A detailed investigation and performance optimization of a photovoltaic panel integrated with a reflecting mirror. (September 2019) - Tabasi, Sanaz; Yousefi, Hossein; Noorollahi, Younes; Aramesh, Mohamad
Highlights: A novel detailed modeling method is presented for PV-mirror integration. Different lighting and shading statuses on the panel are determined and modeled. Genetic algorithm has been employed to find optimum configurations. 14 units with the optimum design can supply energy demand of a medium apartment. Losses due to cell temperature rises are about 1% of the total generated power. Abstract: In this paper, the performance of a photovoltaic panel integrated with a reflecting mirror is investigated. In this regard, the effects of panel and mirror tilt angles, and the mirror length on the system performance are modeled. The cell temperature rises have also been considered. Moreover, by a 3D model, the lighting and shading statuses are studied in detail, and all the possible conditions are presented and modeled. The resulting model can calculate the amount of incident solar energy on the panel and the generated electrical power in every moment during a year. This amount is dependent on the system configuration and capacity and its location. A 250-W photovoltaic panel and the city of Tehran have been considered the basics of calculations to assess the model results. By employing the genetic algorithm method, the optimum configuration has been found to have 69.084° and 0° tilt angles for the panel and the mirror, respectively, at the mirror length of 2 m. This configuration can generate 2.38 GJ (613.89 kWh) of electrical energy annually. It was also found that the optimum configuration had 0.024 GJ of annual energy losses due to the effects of cell temperature rise.